Paleopathological characteristics of Neolithic early rice farmers in the lower reaches of the Yangtze river - Sawada, Junmei; Sun, Guoping; Huang, Weijin; Kubota, Shinji; Saeki, Fumiko; Okazaki, Kenji; Yoneda, Minoru; Nakamura, Shin’ichi (Frontiers in Earth Science, 2023)
Paleopathological investigations of human remains from the Neolithic Hemudu culture in the lower reaches of the Yangtze River in southern East Asia were conducted to clarify the health status of people in early rice-farming societies. Our results show that the occurrence ratios of cribra orbitalia and enamel hypoplasia did not differ significantly between early rice farmers and hunter-gatherers. By contrast, the occurrence ratios of periosteal reactions, dental caries, and antemortem tooth loss in adults were higher among the early rice farmers. Based on these findings and the results of archaeological research on the Hemudu culture, it was suggested that: 1) the Hemudu culture adopted a diversified livelihood strategy that was not overly dependent on rice as a food resource, which did not lead to an extreme decline in health status, 2) the work in the rice fields or the working environment caused stress to the workers, and 3) the rice-farming society's dietary habits led to a decline in oral health. Our results provide new paleopathological insights into the health status of early rice farmers in East Asia. However, the sample size of early rice farmers used in this study was small, and more data are needed to verify the validity of the views presented here.